An accessible pharmacodynamic transcriptional biomarker for notch target engagement. Issue 4 (17th February 2016) - Tanis, KQ; Podtelezhnikov, AA; Blackman, SC; Hing, J; Railkar, RA; Lunceford, J; Klappenbach, JA; Wei, B; Harman, A; Camargo, LM; Shah, S; Finney, EM; et al.
Abstract : γ‐Secretase mediates amyloid production in Alzheimer's disease (AD) and oncogenic activity of Notch. γ‐Secretase inhibitors (GSIs) are thus of interest for AD and oncology. A peripheral biomarker of Notch activity would aid determination of the therapeutic window and dosing regimen for GSIs, given toxicities associated with chronic Notch inhibition. This study examined the effects of GSI MK‐0752 on blood and hair follicle transcriptomes in healthy volunteers. The effects of a structurally diverse GSI on rhesus blood and hair follicles were also compared. Significant dose‐related effects of MK‐0752 on transcription were observed in hair follicles, but not blood. The GSI biomarker identified in follicles exhibited 100% accuracy in a clinical test cohort, and was regulated in rhesus by a structurally diverse GSI. This study identified a translatable, accessible pharmacodynamic biomarker of GSI target engagement and provides proof of concept of hair follicle RNA as a translatable biomarker source.